Transforming biology education: How DECODE cloud model and gender shape TPACK-21 and digital literacy - Sya'rawi, Muhammad Akram; Susanto, Hendra; Suwono, Hadi (Univeritas Papua, 2025)
Digital transformation in education necessitates new competencies for biology teachers. This study examines the influence of the DECODE model integrated with Cloud Classroom and gender on TPACK-21 and digital literacy among biology education students. Using a quasi-experimental design with pretest-posttest nonequivalent control groups, 53 undergraduate students from Universitas Negeri Medan participated in the study. The experimental group (n=26) received the DECODE-Cloud Classroom intervention while the control group (n=27) followed a conventional case study approach. Data collection employed self-report questionnaires, teaching module evaluations, observation sheets, and learning product assessments. MANCOVA analysis revealed that the DECODE-Cloud Classroom model significantly enhanced both TPACK-21 and digital literacy with large effect sizes. Gender showed no significant effect on TPACK-21 but significantly influenced digital literacy development, with male students demonstrating greater improvement in digital security and content creation dimensions, while information and data literacy showed the smallest gap between genders. The interaction between the learning model and gender was not significant for either dependent variable, indicating consistent effectiveness across genders despite varying improvement rates. The findings support implementing the DECODE-Cloud Classroom model in biology teacher preparation programs while considering gender-responsive strategies to optimize digital competency development.